Microglia react to partner loss in a sex- and brain site-specific manner in prairie voles - Pohl, Tobias T. (Brain Behav Immun, 2021)
Positive social relationships are paramount for the survival of mammals and beneficial for mental and physical health, buffer against stressors, and even promote appropriate immune system functioning. By contrast, impaired social relationships, social isolation, or the loss of a bonded partner lead to aggravated physical and mental health. For example, in humans partner loss is detrimental for the functioning of the immune system and heightens the susceptibility for the development of post-traumatic stress disorders, anxiety disorders, and major depressive disorders. To understand potential underlying mechanisms, the monogamous prairie vole can provide important insights. In the present study, we separated pair bonded male and female prairie voles after five days of co-housing, subjected them to the forced swim test on the fourth day following separation, and studied their microglia morphology and activation in specific brain regions. Partner loss increased passive stress-coping in male, but not female, prairie voles. Moreover, partner loss was associated with microglial priming within the parvocellular region of the paraventricular nucleus of the hypothalamus (PVN) in male prairie voles, whereas in female prairie voles the morphological activation within the whole PVN and the prelimbic cortex (PrL) was decreased, marked by a shift towards ramified microglial morphology. Expression of the immediate early protein c-Fos following partner loss was changed within the PrL of male, but not female, prairie voles. However, the loss of a partner did not affect the investigated aspects of the peripheral immune response. These data suggest a potential sex-dependent mechanism for the regulation of microglial activity following the loss of a partner, which might contribute to the observed differences in passive stress-coping. This study furthers our understanding of the effects of partner loss and its short-term impact on the CNS as well as the CNS immune system and the peripheral innate immune system in both male and female prairie voles.